KESETARAAN GENDER DALAM PENDIDIKAN - RUSTAN EFENDY (LPPM IAIN Parepare, 2014)
Essentially education includes the pricples of gender equity biased gender in education results on unobtionable of educational goals. For that reason it is required an equal education where the curriculum of the institution integrates gender within its subject and lectures. One of education goal is how to realize fair society, by not discriminate one sex. But the reality exist discrimination at education that necessitate several effort to solve it, on of it is by formulating curriculum that have gender perspective. Curriculum is a development of vision and mission of educational institution that want to realize education goal. Gender curriculum is based on an assumption that woman and man are equal in education, and have equal opportunity to get education. In its application, gender curriculum can be formulated implicitly (hidden curriculum), or explicitly (overt curriculum). However, to explain gender problems we recommend explicit way.